2012
DOI: 10.1002/adfm.201200489
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Field Magnetoresistance in La0.67Sr0.33MnO3:ZnO Composite Film

Abstract: A nanocomposite fi lm of La 0.67 Sr 0.33 MnO 3 (LSMO):ZnO is synthesized by depositing LSMO solution on a vertical array of ZnO nanorods grown on (0001) Al 2 O 3 substrate. The magnetic behavior of the composite fi lm differs from that of a pure LSMO fi lm, possibly due to smaller grain size in the composite, small amount of Zn doping, or the presence of nonmagnetic ZnO phase near the LSMO grain boundaries. Magnetotransport measurements show that the low-fi eld magnetoresistance (LFMR) of the nanocomposite fi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Moreover, the peak resistivity of these two composite films (0.59 Ω•cm for LCMO:10%-NiO and 1.07 Ω•cm for LCMO:10%-Co 3 O 4 at zero magnetic field) are much higher than that of the single phase LCMO film (0.0061 Ω•cm at zero magnetic field). These two observations can be attributed to the presence of a large number of the grain boundaries, increased disorder, as well as insulating phase-induced barriers to the electrical transport14313233. The introduced insulating phase at the grain boundary has been known to obstruct the magnetic spin alignment near the grain boundary region.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the peak resistivity of these two composite films (0.59 Ω•cm for LCMO:10%-NiO and 1.07 Ω•cm for LCMO:10%-Co 3 O 4 at zero magnetic field) are much higher than that of the single phase LCMO film (0.0061 Ω•cm at zero magnetic field). These two observations can be attributed to the presence of a large number of the grain boundaries, increased disorder, as well as insulating phase-induced barriers to the electrical transport14313233. The introduced insulating phase at the grain boundary has been known to obstruct the magnetic spin alignment near the grain boundary region.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the resistivity increases for the LCMO:30%-Co 3 O 4 composite film in comparison to that of the LCMO:10%-Co 3 O 4 composite film. This is because the metal-insulator transition was suppressed by the expansion of in-plane lattice parameter in LCMO1422.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…What is more, in the past few years the effect of grain boundaries in LSMO has been studied intensively [5]- [8]. It was found that the secondary phase at the boundary not only can lead to a large low field magnetoresistance (LFMR) but also a large change in the intrinsic magnetic properties, i.e., the ferromagnetic transition temperature ( ) and the coercive field ( ) at low temperature [9], [10]. Although the doping effects of the nano-impurities on the electrical and magnetic properties in the bulk composite samples have been investigated by several groups [11]- [13], the magnetic interaction at the boundaries Manuscript (EB effect) and magnetotransport behaviors of the nanocomposite thin films has rarely been studied [14].…”
Section: Introductionmentioning
confidence: 99%